World Economic and Financial Surveys : International Capital Markets 1994. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1994)
This paper analyzes the origins of the recent turbulence in government bond markets in the major industrial countries, and considers whether the role of hedge funds in that episode argues for altering present regulatory arrangements. In financial markets, it is possible for such a revision of expectations-if it is shared by all market participants-to alter asset prices almost immediately; indeed, the change in asset prices can occur without any transactions even taking place. In this case, however, trading volumes soared along with the rise in bond yields, as a broad spectrum of market participants sought to undo large positions that had been built up under the projections of a continued rise of European and US bond prices and a strengthening of the dollar against the yen and some European currencies. Although the increase in bond yields was undeniably large for such a short time period, the markets did receive new information in February and March on economic performance-especially on growth rates-and on the likely future course of macroeconomic policies.